Letter (copy) : Homes for Spanish children - Tewson, Vincent
030-0081-001 Secretary's. HVT/FC/EK/1748. 30th August, 1938. Mr. E. Edwards, Mineworkers' Federation of Great Britain, 50, Russell Square, London, W.C.1. Dear Mr. Edwards, HOMES FOR SPANISH CHILDREN. I have now heard from the International Federation of Trade Unions that the material for the two homes which are being set up on behalf of the Mineworkers' Federation is being dispatched this week. I think you will agree that Mr. Schevenels has not lost any time in getting on with the job, and I am hopeful that when he arrives at Congress he will be in possession of a report showing that the homes are ready for occupation. We must try and arrange some contact with representatives of your Sub-Committee and with Mr. Schevenels during Congress week. Yours sincerely, Assistant Secretary. 292/946/30/81